Fraud and Corruption Cases and Materials - Smith, Duncan (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book discusses and analyses fraud and corruption cases from many industries including construction, finance, pharmaceutical, transport, retail, medical, health, communication, education and military. The book is divided into two sections. The first part presents case studies that cover several industry sectors, including not only well-known frauds like Bernie Madoff, Wells Fargo and the Enron case, but also recent events such as the Theranos/Elisabeth Holmes case. The second section of the book includes materials on fraud and corruption such as the full text of the United Nations Convention Against Corruption, the OECD Convention on Combating Bribery of Foreign Public Officials in International Business, and the EIB's Anti-Fraud Policy and Whistleblowing Policy. It also includes examples about current corporate anti-corruption policies from companies like Apple, Tesla and Coca Cola. For interested readers, the book offers additionally a list of films that realistically cover the topics fraud, corruption and whistleblowing.
Keywords: Corporate governance; International finance; Business ethics; Industries; Commercial law; Corporate Governance; International Finance; Business Ethics; Industries; Business Law